Accidental poisoning of wild geese in Perthshire, November 1971 - Bailey, S; Bunyan, P J; Hamilton, G A; Jennings, D M; Stanley, P I (Wildfowl, 1972)
Following the autumn sowing of wheat dressed with carbophenothion and a mercurial fungicide in an area of Perthshire visited by Greylag Geese Anser anser some hundreds of the birds were found dead. Analytical and biochemical investigations gave results which were consistent with poisoning by carbophenothion. Conclusions are drawn about this incident and some suggestions made to reduce risks in future.